CONTRIBUTION OF THOUGHTS OF ACEH TAMIANG FIGURES IN BUILDING DEMOCRACY ELECTIONS FREE FROM MONEY POLITICS - Hakim, Lukmanul (NOMOI Law Review, 2025)
The practice of money politics is a serious challenge in the democratic system in Indonesia, including in Aceh Tamiang, which can damage the essence of democracy and worsen the quality of elections. In this case, voters tend to be influenced by material incentives, not by the quality of candidates or the vision and mission offered, which results in reduced election integrity. In addition, social inequality is increasing because only those with material resources can dominate the election process. Aceh Tamiang, as a region with the implementation of Islamic Sharia, has great potential to build a democracy with integrity. This study aims to explore the contribution of the thoughts and strategies of community leaders, such as religious, educational, and traditional leaders, in minimizing the practice of money politics in the area. This research uses an empirical legal research method with a statute approach and case study. The results of the study show that even though there are qanuns that support fair elections, the practice of money politics continues to occur, mainly due to poverty and lack of political education. Religious, educational, and traditional leaders in Aceh Tamiang play an important role in preventing this practice, through voter education, strengthening law enforcement, and transparency of campaign funds, to realize a democracy free from money politics.